Edukasi Pengelolaan Sampah Plastik Berbasis PAR di Dusun Krasak: Intervensi Tiga Level Menuju Desa Berkelanjutan - Hakim, Faisol; Ulum, M. Bustanul; Fauzi, Muhammad Fikri (Universitas Islam Internasional Darullughah Wadda'wah, 2026)
Plastic waste management in rural areas remains an unsystematic environmental challenge in Indonesia. Krasak Hamlet, Pancakarya Village, Ajung District, Jember Regency faces a waste emergency: no adequate disposal site, no village regulation, and low community awareness. This research-based community service (PkM-BR) applies Participatory Action Research (PAR) integrated with a three-level intervention framework—individual, community, and institutional. Activities involved ±80 residents across four cyclical stages. Results: 83.3% of FGD participants understood the sanitation–stunting correlation; 80% committed to waste sorting by day 7; five critical waste sites were fully cleaned; and the village head issued a written commitment to allocate Village Fund resources for waste facilities and draft a Village Regulation. This programme contributes to SDGs Goal 11 and Goal 3.